Understanding digital libraries - Lesk, Michael; Lesk, Michael (Amsterdam ; Boston : Elsevier, 2005)
This fully revised and updated second edition of Understanding Digital Libraries focuses on the challenges faced by both librarians and computer scientists in a field that has been dramatically altered by the growth of the Web. At every turn, the goal is practical: to show you how things you might need to do are already being done, or how they can be done. The first part of the book is devoted to technology and examines issues such as varying media requirements, indexing and classification, networks and distribution, and presentation. The second part of the book is concerned with the human contexts in which digital libraries function. Here youll find specific and useful information on usability, preservation, scientific applications, and thorny legal and economic questions. -- Publisher description.
1. Evolution of libraries -- 2. Text documents -- 3. Images of pages -- 4. Multimedia storage and retrieval -- 5. Knowledge representation schemes -- 6. Distribution -- 7. Usability and retrieval evaluation -- 8. User needs -- 9. Collections and preservations -- 10. Economics -- 11. Intellectual property rights -- 12. A world tour of digital libraries -- 13. Scope of digital libraries -- 14. Future : ubiquity, diversity, creativity, and public policy.
"Practical digital libraries, 2nd edition."
Includes bibliographical references (pages 387-411) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Libraries -- Special collections -- United States -- Computer files; Digital libraries -- United States; Bibliothèques -- États-Unis -- Fonds spéciaux -- Fichiers (Informatique); Bibliothèques virtuelles -- États-Unis.; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Libraries -- Special collections -- Computer files; Digital libraries; United States